Clinical Impact of Changes in Left Ventricular Function After Aortic Valve Replacement. Issue 8 (25th August 2015) - Une, Dai; Mesana, Laura; Chan, Vincent; Maklin, Michelle; Chan, Ryan; Masters, Roy G.; Mesana, Thierry G.; Ruel, Marc
<x xml:space="preserve">Abstract</x> Background— Our objectives were to identify correlates of mortality and congestive heart failure after aortic valve replacement (AVR) according to preoperative left ventricular (LV) function and to describe the incidence, time course, and correlates of LV recovery and mass regression postoperatively. Methods and Results— A total of 3112 patients with AVR were assessed in a follow-up clinic with echocardiography (median follow-up, 6.0 years). At operation, their mean age was 67.8±13.4 years, one third were female, and 29% had LV dysfunction (ejection fraction <50%). In severe patients with severe aortic stenosis and LV dysfunction, transaortic valve mean pressure gradient <40 mm Hg, longer cardiopulmonary bypass duration, and prosthesis-patient mismatch (indexed effective orifice area ⩽0.85 cm2/m2) were independent correlates of the composite outcome of death or congestive heart failure after AVR. In patients with severe aortic regurgitation and LV dysfunction, older age and higher preoperative LV mass were identified. LV recovery correlated with better survival and freedom from heart failure in patients with aortic stenosis. Maximum LV mass regression took 24 months in patients with aortic stenosis and nearly 5 years with aortic regurgitation; independent correlates included smaller LV end-systolic diameter in patients with aortic stenosis and low New York Heart Association class with aortic regurgitation. Conclusions— Incomplete LV recovery, prosthesis-patient mismatch, low transaortic valve pressure gradient, and higher LV mass are associated with increased mortality or heart failure after AVR in patients with LV dysfunction. Higher LV end-systolic diameter and symptoms correlate with less LV mass regression, which takes at least 2 years. These findings help surgeons and cardiologists refine the indications, timing, prognostication, and follow-up of patients before and after AVR.